Perlindungan Hukum terhadap Barang Kiriman Konsumen Pengguna Jasa Go-Send Instant Courier Melalui Tokopedia - Rochati Mahfiroh (Universitas Islam Indonesia, 2020)
Information technology can be a double-edged sword, because in addition to contributing to the improvement of welfare and the advancement of human civilization, it can also be an effective means of illegal acts. In the context of online transportation, amongst the services provided by Go-Jek Indonesia, Go-Send is the most prone to law violations. This research is a qualitative study with an empirical juridical approach. The object of research is the case of lost goods in the use of the Go-Jek Gosend Instant Courier delivery service feature in the largest marketplace channel in Indonesia, namely Tokopedia. This research attempts to answer questions about Go-Jek and Tokopedia's responsibility for the loss of consumer goods and legal efforts that can be taken if the security of the goods is not fulfilled. Based on the results, it is concluded that Tokopedia and Go-Jek are legally responsible for the loss of goods when transporting goods through Go-Send Instant Courier ordered through the Tokopedia application. Both of them are responsible according to the principle of fault liability. Consumers can take three legal routes: First, file a complaint through the complaint feature provided by Tokopedia; Second, file a lawsuit to BPSK; Third, file a civil suit to the District Court.